2000
DOI: 10.1103/physrevlett.84.6010
|View full text |Cite
|
Sign up to set email alerts
|

Self-Similar Propagation and Amplification of Parabolic Pulses in Optical Fibers

Abstract: Ultrashort pulse propagation in high gain optical fiber amplifiers with normal dispersion is studied by self-similarity analysis of the nonlinear Schrödinger equation with gain. An exact asymptotic solution is found, corresponding to a linearly chirped parabolic pulse which propagates self-similarly subject to simple scaling rules. The solution has been confirmed by numerical simulations and experiments studying propagation in a Yb-doped fiber amplifier. Additional experiments show that the pulses remain parab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
431
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 738 publications
(451 citation statements)
references
References 15 publications
17
431
0
3
Order By: Relevance
“…Output temporal width can be continuously varied over a wide range, from 50 ps to 250 ps. The experimental results are in good agreement with a fit based on a E ini 1/3 function which is typical of the selfsimilar analytical evolution of the parabolic pulses [1]. However let us note that for pulse durations below 100 ps, the asymptotic parabolic profile is not fully reached.…”
Section: Experimental Set-upsupporting
confidence: 77%
See 2 more Smart Citations
“…Output temporal width can be continuously varied over a wide range, from 50 ps to 250 ps. The experimental results are in good agreement with a fit based on a E ini 1/3 function which is typical of the selfsimilar analytical evolution of the parabolic pulses [1]. However let us note that for pulse durations below 100 ps, the asymptotic parabolic profile is not fully reached.…”
Section: Experimental Set-upsupporting
confidence: 77%
“…Experimental demonstrations have been carried out both in rare-earth doped fibres (with Ytterbium [1] and Erbium [2] dopants) as well as in Raman fibre amplifiers [3]. The use of frequency resolved optical gating (FROG) technique based on iterative algorithms has enabled a precise but indirect intensity and phase characterisation of the amplified pulses which exhibit a parabolic intensity profile combined with a strictly linear chirp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic parameters of the similariton (peak power, temporal and spectral widths) then undergo an exponential increase with the propagation distance. A remarkable feature that constitutes a clear advantage for regeneration purpose 29) is that this asymptotic profile does only depend on the initial pulse energy and not on the details of the initial pulse shape 30,34) .…”
Section: Principle Of Operation and Configuration Under Studymentioning
confidence: 99%
“…Indeed, it has been demonstrated that any initial waveform propagating under conditions of normal dispersion, non-linearity and distributed gain will evolve asymptotically into a similariton, a pulse characterized by a parabolic intensity profile with a linear positive chirp [30][31][32] . Once this typical parabolic profile is obtained, it propagates self-similarly, i.e.…”
Section: Principle Of Operation and Configuration Under Studymentioning
confidence: 99%